KAJIAN IMPLIKASI HUTANG PADA KINERJA PERUSAHAAN DAERAH AIR MINUM (PDAM) KABUPATEN PURBALINGGA - Suwaryo Suwaryo (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2012)
The study entitled ”The Study of Debt Implications on Performance of Purbalingga Drinking Water Company (PDAM)” aims to identify and analyze the condition of Purbalingga PDAM debt, debt management performance in PDAM Purbalingga, financial performance and operational performance. Data obtained by doing library research and interviews. The data used in the form of secondary data obtained from PDAM Purbalingga. To know and analyze the condition of PDAM debt Purbalingga used descriptive analysis using data tabulation. To know and analyze the performance of debt management used financial ratios Debt to Total Asset Ratio, DER, ROI, ROE and Cost of principal repayment and interest expenses are analyzed using data tabulation. To know the financial and operational performance of PDAM Purbalingga used ratio analysis according to Kep.Mendagri No. 147, tahun 1999. The research concluded that during the study period PDAM Purbalingga short-term debt burden is very large due liabilities to long-term debt maturities. The average number of debt to total assets ratio of 0.5, DER of 1.12, an ROI of 3.37 percent, ROE of 7.05 percent, and based on the analysis of principal and interest expense is known that the average principal repayment and mature flowers are borne PDAM Purbalingga during the study period amounted to USD. 5,215,715,190.81 only a little difference to the overall operational costs are borne by PDAM Purbalingga Rp. 8,101,085,750.91. Assessment of financial and operational performance of PDAM Purbalingga rated "sufficient" while the operational performance is considered "poorly".